2010
DOI: 10.1094/ats-2010-0312-03-rs
|View full text |Cite
|
Sign up to set email alerts
|

Early Curative Dollar Spot Control in Creeping Bentgrass as Influenced by Fungicide Spray Volume and Application Timing

Abstract: The importance of spray volume and application timing of a fungicide targeting dollar spot (Sclerotinia homoeocarpa F. T. Bennett) has been investigated, but with conflicting results. The objectives of this field study were to assess the influence of two spray volumes (468 and 935 liters water/ha) and two application timings (AM to a canopy wet with dew versus PM to a dry canopy) for fungicides targeting dollar spot curatively. Chlorothalonil (8.5 kg a.i./ha), propiconazole (0.5 kg a.i./ha), and a tank‐mix of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In a separate study, Cropper's (5) field experiments suggested that an early curative program performed better than a curative program based on an action threshold of 20% disease severity, although those curative approaches were not directly compared in the same experiment. Pigati et al (10) evaluated application volume and timing (AM vs. PM) as well as product efficacy under early curative conditions but did not compare an early curative program to alternative timing approaches. In limited testing in Indiana, a spray threshold of <1% damage provided acceptable dollar spot control on fairway‐height creeping bentgrass, which was not the case with a 3 to 4% threshold (8).…”
Section: Introductionmentioning
confidence: 99%
“…In a separate study, Cropper's (5) field experiments suggested that an early curative program performed better than a curative program based on an action threshold of 20% disease severity, although those curative approaches were not directly compared in the same experiment. Pigati et al (10) evaluated application volume and timing (AM vs. PM) as well as product efficacy under early curative conditions but did not compare an early curative program to alternative timing approaches. In limited testing in Indiana, a spray threshold of <1% damage provided acceptable dollar spot control on fairway‐height creeping bentgrass, which was not the case with a 3 to 4% threshold (8).…”
Section: Introductionmentioning
confidence: 99%